Effects of payment methods on shareholder’s wealth and the determinants of payment choices - Tiansheng, Zhu (2016)
This study utilized the empirical methodologies to examine the impacts of M&A on shareholder wealth, and determinants of payment choices in M&A deals. The sample is of 338 M&A from 2006 to 2016 by Asia-Pacific listed firms who have successfully completed the transactions.